Caracterización de la mosca de la fruta en el cultivo de mora (rubus glaucus) en el cantón Sigchos provincia de Cotopaxi 2022 – 2023. - Valiente Licintuña, Walter Remigio (2023)
This investigation was carried out at Cantera community in Sigchos canton, Cotopaxi province, to monitor the presence of the fruit fly (Anastrepha spp. and Ceratitis capitata) in blackberry crops at an altitude ranging from 2605 to 2804 m.s.n.m. The proposed objectives were to observe whether or not there is a presence of fruit flies to determine the area free of these quarantine pests and to identify the species obtained in the traps during the monitoring process, making visual and photographic observations to classify them more easily all samples are observed in the plant protection laboratories of the Technical University of Cotopaxi. The descriptive, qualitative, and quantitative research methods were used; the Shannon diversity index methodology was applied, as well as the Sorensen methodology. To monitor, the Georeferencing of the trapping points was established using McPhail-type traps; on the other hand, it was used sugarcane molasses dissolution baits. The results obtained after 12 monitoring shows that in the Cantera community, there is no presence of the pest under study, while the diversity of insects was calculated using the Shannon-Wiener diversity index method, giving a result equal to 1 Low Diversity, Sorensen's methodology was applied with which it was found that the percentage of insects during the four months is 90%. Based on this study, it is concluded that the Cantera community can be declared, at the moment, as a fruit fly-free area, and the species that most predominate in the crop are the domestic musca and the hepialus humulis.